2021
DOI: 10.1186/s12940-021-00693-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of wind in human illness due to pesticide drift in Washington state, 2000–2015

Abstract: Background Pesticides play an important role in protecting the food supply and the public’s health from pests and diseases. By their nature, pesticides can be toxic to unintended target organisms. Changing winds contribute to pesticide drift— the off-target movement of pesticides—and can result in occupational and bystander illness. Methods We systematically linked historical weather data to documented pesticide drift illnesses. We used Washington … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
1
0
2
Order By: Relevance
“…These findings are consistent with recent studies that have shown that urban sprawl towards agricultural fields can result in an increased risk of pesticides drifting into residential areas [9,32,40,49,54,[61][62][63][64][65][66][67][68]. While the study has its limitations and hypotheses, it provides an accurate evaluation of organophosphate pesticide drift, which can serve as a basis for further in-depth research on drift tendencies.…”
Section: Agdrift Model For Field-level Simulationssupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with recent studies that have shown that urban sprawl towards agricultural fields can result in an increased risk of pesticides drifting into residential areas [9,32,40,49,54,[61][62][63][64][65][66][67][68]. While the study has its limitations and hypotheses, it provides an accurate evaluation of organophosphate pesticide drift, which can serve as a basis for further in-depth research on drift tendencies.…”
Section: Agdrift Model For Field-level Simulationssupporting
confidence: 89%
“…To explore the impact of pesticide drift on the environment and community well-being, especially in counties that lack pesticide usage records, previous studies have used GIS and satellite imagery. Their approach and findings will be more relevant and useful at a county-wide level, such as in Sangamon County [57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…En primer lugar, señala la deriva primaria como aquella que se produce durante la aplicación. Ésta es la más estudiada y para la cual existen múltiples recomendaciones y mejoras tecnológicas para minimizarla (Etiennot y Piazza, 2010;Kasner et al, 2021;Merani et al, 2019;SADER, 2019).…”
Section: Escala De Vientos Beaufortunclassified
“…Sin embargo, estas dificultades no hacen menos real el problema. En zonas de agricultura intensiva en Estados Unidos, como los estados de California, Washington y Nebraska, se documentan eventos recurrentes de deriva que afectan a la población colindante (Lee et al, 2002;VoPham et al, 2015;Lindsey, 2011;Kasner et al, 2021;Wan, 2015). En la provincia de Córdoba, en Argentina, se denunció la exposición de la población urbana a la deriva de diversos plaguicidas entre los años 1997 y 2008, para lo cual se establecieran límites de distancias para la aplicación terrestre y aérea (Bonaparte et al, 2012;Tomasoni, 2013).…”
Section: Introductionunclassified